Lactoferrin: A Roadmap to the Borderland between Caries and Periodontal Disease. (June 2015) - Fine, D.H.
Lactoferrin is one of a number of multifunctional proteins that are present in or on all mucosal surfaces throughout the body. Levels of lactoferrin are consistently elevated in inflammatory diseases such as arthritis, inflammatory bowel diseases, corneal disease, and periodontitis. Single-nucleotide polymorphisms (SNPs) in lactoferrin have been shown to be present in individuals susceptible to Escherichia coli –induced travelers' diarrhea and in tear fluid derived from virally associated corneal disease. Here, we review data showing a lactoferrin SNP in amino acid position 29 in the antimicrobial region of lactoferrin that acts against caries associated bacteria. This SNP was initially discovered in African American subjects with localized aggressive periodontitis (LAP) who had proximal bone loss but minimal proximal caries. Results were confirmed in a genetic association study of children from Brazil with this same SNP who showed a reduced level of caries. In vitro data indicate that lactoferrin from whole saliva derived from subjects with this SNP, recombinant human lactoferrin containing this SNP, or an 11-mer peptide designed for this SNP kills mutans streptococci associated with caries by >1 log. In contrast, the SNP has minimal effect on Gram-negative species associated with periodontitis. Moreover, periodontally healthy subjects homozygous for this lysine (K) SNP have lactoferrin in their saliva that kills mutans streptococci and have reduced proximal decay. The review summarizes data supporting the ecologic plaque hypothesis and suggests that a genetic variant in lactoferrin with K in position 29 when found in saliva and crevice fluid can influence community biofilm composition. We propose that, for caries, this SNP is ethnicity independent and protective by directly killing caries-provoking bacteria (reducing proximal decay). However, the clinical effect of this SNP in LAP is ethnicity dependent, destructive (increases LAP incidence), and complex with mechanisms still to be determined.